2018
DOI: 10.1038/s41586-018-0357-y
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature electrical control of exciton flux in a van der Waals heterostructure

Abstract: Devices that rely on the manipulation of excitons-bound pairs of electrons and holes-hold great promise for realizing efficient interconnects between optical data transmission and electrical processing systems. Although exciton-based transistor actions have been demonstrated successfully in bulk semiconductor-based coupled quantum wells, the low temperature required for their operation limits their practical application. The recent emergence of two-dimensional semiconductors with large exciton binding energies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
484
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 420 publications
(497 citation statements)
references
References 35 publications
9
484
3
1
Order By: Relevance
“…The reduced overlap of the electron-hole wavefunctions entails greatly prolonged exciton lifetimes of more than 100 ns [10,12], exceeding the lifetime of intralayer excitons by several orders of magnitude [13,14]. The long lifetimes enable the formation of thermalized dense exciton ensembles [15], which, together with IX diffusion over several micrometers [16,17], sets up the possibility to operate excitonic devices [16,18].…”
mentioning
confidence: 99%
“…The reduced overlap of the electron-hole wavefunctions entails greatly prolonged exciton lifetimes of more than 100 ns [10,12], exceeding the lifetime of intralayer excitons by several orders of magnitude [13,14]. The long lifetimes enable the formation of thermalized dense exciton ensembles [15], which, together with IX diffusion over several micrometers [16,17], sets up the possibility to operate excitonic devices [16,18].…”
mentioning
confidence: 99%
“…[46] It has been shown that energy transfer by excitons can be described by a Dexter triplet-to-triplet (exchange) mechanism with multistep incoherent exciton hopping, or a Förster mechanism involving one-step jumping over longer distances. [42] An ability to generate excitons by light, and electrical control of these excitons, also supports MOF application in optoelectronics in the near future, [56] and we believe that MOFs can compete with materials such as inorganic 2D vdW crystals and heterostructures, [57] organic polymers, and crystals for micro-and nano-electronic devices that operate based on the Bose-Einstein condensation effect. [55] Intriguingly, the structure of MOFs also affects the exciton migration path, as it was discovered that mixed Ru/Os structures constituted 1D or 3D hopping networks.…”
Section: Excitonsmentioning
confidence: 71%
“…The monolayer semiconducting transition metal dichalcogenides (MoS 2 , WS 2 , MoSe 2 , and WSe 2 ) exhibit strongly bound two-dimensional excitons with a binding energy on the order of few hundreds of meV, making these ultra-thin monolayers an excellent test bed for excitonic manipulation even at room temperature [1][2][3][4][5]. The neutral excitons (X 0 ) show excellent valley polarization and valley coherence properties that can be readily probed through initialization by circularly and linearly polarized photons, respectively, followed by detection through a circular or linear analyzer [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, this problem has been addressed by creating inter-layer exciton [20][21][22][23][24] to suppress the fast radiative decay, and exciton transport over several micrometer in the plane of the layered material has been demonstrated [4]. An external gate control has also been achieved by modulating the binding energy of the neutral exciton [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation